Multi-segments conformal plan optimization for head and neck cancer - Doaa Ali Salih Khudair; Haydar Hamza Obaid Alabedi; Nabaa Mohammad Ali Ahmed Alazawy (Journal of the Pakistan Medical Association)
Objective: To evaluate better dose distribution with three-dimensional radiation therapy, and to compare it with multi-segmented treatment planning techniques in patients with head and neck cancer.